Nietzsche e la morfologia. Nietzsche and Morphology (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
L’influenza che il pensiero di Goethe scienziato e della morfologia hanno avuto nella formazione della riflessione nietzschiana costituisce un capitolo fondamentale per ricostruire la genesi di alcuni dei suoi concetti più rilevanti. Tale influenza, infatti, permette di ricostruire le origini delle suggestioni da cui il giovane Nietzsche si è mosso, approfondite successivamente attraverso le novità apportate dalla biologia a lui contemporanea; sfruttando  il terreno fertile della riflessione goethiana, essa ebbe modo di compiersi nella formulazione del concetto di vita come volontà di potenza: quest’ultimo perfeziona, trascrivendoli, tutti gli elementi della riflessione goethiana sul vivente: forma, metamorfosi, divenire, entità vivente, individuo-plurale.Goethe’s thought as a scientist and Morphology have had a pivotal influence on Nietzsche’s thinking. Indeed they are necessary chapters to go through in order to understand how some of the key points of his thought have developed. Understanding how these factors are tangled to Nietzsche's speculation allows to rebuild the origin of suggestions from which the young Nietzsche moved from to examine the new impulses brought by biology. Moreover, it is remarkable to notice that the concept of Life as Will to Power sprout up right from these ideas. In particular, Nietzsche's Will to Power accomplished all the elements present in Goethe's considerations on living: Form, Metamorphosis, Becoming, living entity, plural-Individual.